ANALISIS PERBANDINGAN KINERJA PROTOKOL ON-DEMAND ROUTING PADA JARINGAN SENSOR NIRKABEL AD HOC - Putri, Rizky Ananto; Jusak, Jusak; Sukmaaji, Anjik (Journal JCONES, 2013)
Some of developing countries recently employ network applications that use sensor nodes, Wireless Sensor Networks (WSN) for remote sensing. Most latest researchers, utilize methods with a network topology that has a fixed position. On the other hand, for remote monitoring network set up wireless networks typically use ad hoc and irregular distributed by its users. A study needed to create a network system with randomly generated positions. In this work we concern about wireless network that employ On Demand Routing Protocols, i.e. Ad Hoc On-Demand Distance Vector (AODV) and Dynamic Source Routing (DSR). The result of the research shows that DSR has a better performance in term of delay and packet loss ratio compared to the AODV. On the other hand, AODV shows a better performance in term of bandwidth utilization.